Predictors of response to endobronchial coil therapy in patients with advanced emphysema - Slebos, Dirk-Jan; Herth, Felix (Chest, 2019)
Background - The Lung Volume Reduction Coil Treatment in Patients With Emphysema (RENEW) trial reported improvements in quality of life, pulmonary function, and exercise performance following endobronchial coil treatment. - Objectives - The purpose of this post hoc analysis was to identify baseline predictors, including quantitative CT measures, that identify patients most likely to significantly benefit from endobronchial coil therapy. - Methods - Quantitative CT analysis by an independent radiology laboratory and a qualitative evaluation by five blinded experts of the baseline thoracic CT imaging were performed. Univariate and multivariate logistic regression analyses were performed to elucidate characteristics associated with clinical response. - Results - In total, 125 patients underwent coil treatment and had evaluable 12-month follow-up results. Of these, 78 patients received treatment of lobes with the highest emphysematous destruction determined by quantitative CT analysis (quantitative visual match [QVM]+), and 47 received treatment in at least one lobe that was not the most destroyed (QVM-). From the 78 patients with QVM+ treatment, a subgroup of 50 patients (64%) was identified with baseline residual volume > 200% predicted, emphysema score > 20% low attenuation area, and absence of airway disease. In this subgroup, greater lobar residual volume reduction in the treated lobes was achieved, which was associated with significant mean ± SE improvement in FEV1 (15.2 ± 3.1%), St. George’s Respiratory Questionnaire (-12 ± 2 points), and residual volume (-0.57 ± 0.13 L). - Discussion - This post hoc analysis found that both significant hyperinflation (residual volume ≥ 200% predicted) and CT analysis are critical for patient selection and treatment planning for endobronchial coil therapy. Quantitative CT analysis is important to identify optimal lobar treatment and to exclude patients with insufficient emphysema (< 20% low attenuation area), whereas visual assessment identifies patients with signs of airway disease associated with worse outcomes. - Trial Registry - ClinicalTrials.gov; No.: NCT01608490; URL: www.clinicaltrials.gov.
Gesehen am 27.03.2020